Insider Trading in Credit Derivatives: Evidence From the Credit Default Swap Market - Pekkola, Ville (My University, 2015)
Informed trading exists in most markets, but might be more tempting in some markets than in others. Credit derivatives, and especially the credit default swap (CDS) market, have recently been in the center of speculation as being one of the more tempting markets. What makes the CDS market so intriguing for the informed trader is the opacity and lack of regulation that make monitoring and controlling extremely difficult for the authorities. The purpose of the thesis is to study the existence of potential insider trading in the credit default swap market and to compare the results to those of the stock market by investigating both, the target, and the acquirer insider trading strategies prior to public M&A announcements in the United States. The study is conducted using event studies measuring the cumulative abnormal returns of 41 M&A announcements during and after the financial crisis (2007-2010). The thesis finds strong indication of potential insider trading in the CDS market, as approximately 60 % of the total, after the announcement, price effect occurs prior to the public announcement. No evidence of informed trading is found in the stock market. However, by removing the volatile banking sector announcements from the sample data, the stock market results change significantly, as both the CDS and the stock market report highly statistically significant abnormal returns. Moreover, the results indicate that insider trading could have transitioned from the stock market to the less regulated CDS market during the financial crisis. In addition, there seems to be a general tendency for the CDS market to lead the stock market in abnormal returns.
Keywords: Insider trading; information asymmetry; credit derivatives; credit default swap; event study; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; fi=Master's Degree Programme in Finance|